MEMAHAMI EKSISTENSI DAN TANTANGAN MIE PANGSIT SIANTAR: SEBUAH KAJIAN BUDAYA KULINER DAN STRATEGI PENGEMBANGAN USAHA - Pramuda Sinaga,; Shelina Eka Putri,; Lila Pelita Hati,; Lestari Dara Cinta Utami Ginting, (Jurnal Cakrawala Ilmiah, 2024)
Dumpling noodles are one of the favorite culinary in the city of Pematang Siantar. Dumpling noodles are one of the foods that are sought after by tourists who visit or stop by Siantar city. In addition, dumpling noodles are also one of the most widely sold foods in Siantar. Dumpling noodles are famous for having a delicious and unique taste, with fried dumplings as an additional topping that gives a savory taste. This culinary has become an important part of the culinary culture in the city of Pematang Siantar and is often a popular food choice among locals and visiting tourists. This journal aims to examine the existence of dumpling noodles in Siantar city and what distinguishes them from dumpling noodles outside the Siantar area. This study uses a qualitative approach and data collection through interviews, observation, and documentation. With these data collection techniques, researchers will compile information and combine it with written data such as journals, theses, and online articles. That way, researchers can collect, develop, and organize the information obtained. The results of the study are expected to provide a deeper understanding of the role of dumpling noodles in the culinary culture of the city of Pematang Siantar and the factors that influence its existence.